PERAN BAHASA INDONESIA DALAM BRANDING DAN PEMASARAN INDUSTRI KREATIF: PERSPEKTIF LINGUISTIK BERDASARKAN PERSEPSI MAHASISWA - Imam Safii; Sobri Sobri; Reni Warpitasari (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
Language plays a strategic role in shaping brand image and conveying cultural values in the creative industry. This study aims to analyze students' perceptions of the role of Indonesian in branding and marketing the creative industry from a linguistic perspective. The study employed a descriptive quantitative approach with a survey of 173 students. The research instrument was a five-level Likert-scale questionnaire that measured the communicative, cultural, linguistic, and ideological functions of Indonesian in branding. Data were analyzed using descriptive statistics in the form of mean scores and standard deviations. The results indicate that students have a positive perception of the role of Indonesian in creative industry branding, with average scores ranging from agree to strongly agree. Indonesian is perceived as effective in representing local cultural values, facilitating the understanding of marketing messages, and shaping brand image and memorability through choice of diction and language creativity. However, respondents also demonstrated a pragmatic attitude, agreeing with the use of a combination of Indonesian and a foreign language as a strategy to increase product competitiveness in the global market. This study concludes that Indonesian holds a strategic position as a linguistic resource in creative industry branding and needs to be strengthened through the role of education and the development of applied linguistic literacy.